Separation characteristics of porous polymer packings with reduced particle diameter for HPLC - OKAJIMA, Yoshiaki; MIYAGI, Hiroyuki; MIZUNO, Masako; MIURA, Junkichi (BUNSEKI KAGAKU, 1988)
Performances of 2 μm porous polymer packings, styrene-divinylbenzene co-polymer (S-DVB) and S-DVB with quaternary ammonium were presented. Correlation between chromatographic preformances and physical properties such as specific surface area and ion exchange capacity was studied. The column packed with 2 μm S-DVB showed 12 μm of height equivalent to a theoretical plate (HETP), which was 50 and 30% decrease as compared with 6 μm and 3 μm respectively. The column packed with S-DVB with quaternary ammonium of 2 μm or 3 μm showed 10 μm of HETP, which was 50% decrease as compared with 6 μm. By decreasing the particle diameter less than 3 μm, improvement of chromatographic efficiency was not clear. It was suggested that the minimum possible particle diameter of porous polymer packings was 23 μm for HPLC.